2014
DOI: 10.3141/2429-03
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Escorting Children to School in Modeling Individual Daily Activity Patterns of Household Members

Abstract: Escorting children to school is a common travel arrangement in a household with schoolchildren. This escorting task affects travel patterns of the adult household members as accommodations are made for dropping children off at school or picking them up or doing both. Approaches to modeling joint travel arrangements between adults and children with respect to escorting have been previously suggested. However, examples of implementing such models in the framework of an operational activity-based model (ABM) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…According to involved participants and their different intra-household interactions, household activities can be classified into joint, independent and allocated activities [3,6,18]. The study on the joint activity, which typically reflects the intra-household interactions among household members, dominates household activities-related research [8,[44][45][46][47]. The allocated activity is usually not addressed or equivalent to the independent activity in existing research [5,6], since only one household member participates in the activity.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…According to involved participants and their different intra-household interactions, household activities can be classified into joint, independent and allocated activities [3,6,18]. The study on the joint activity, which typically reflects the intra-household interactions among household members, dominates household activities-related research [8,[44][45][46][47]. The allocated activity is usually not addressed or equivalent to the independent activity in existing research [5,6], since only one household member participates in the activity.…”
Section: Plos Onementioning
confidence: 99%
“…The elderly couples would like to go shopping or leisure jointly and enjoy the company of each other. Some evidences suggest that the longer time they spend together during non-compulsory activities, the more satisfactions they will gain [ 5 , 45 ].…”
Section: Empirical Analysismentioning
confidence: 99%
“…The emphasis on understanding the school-commuting behavior can be traced to 1990 in which Hillman et al (1990) reported that the independent mobility of students had sharply dropped from 80 percent to 9 percent between 1971 and 1990 in the UK. More recently, school-commuting behavior has received attention, given its potential link to travel patterns of the parents and other adult household members Gupta et al, 2014).…”
Section: Literature Synthesismentioning
confidence: 99%
“…However, although the topic has been widely discussed in the literature, relatively few large-scale applications have been performed. Notable examples of such applications occurred in Portland, Oregon (11), San Francisco, California (12), New York (13), Phoenix and Tucson, Arizona (14,15), the Netherlands (16) and Switzerland (17).…”
mentioning
confidence: 99%